Hubungan Karakteristik Penyuluh dengan Kinerja Penyuluh di Kecamatan Sampara Kabupaten Konawe - Sitti Rosmalah; Rayuddin; Hartati; Basri Sufa (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
The performance of agricultural extension workers is the level of work success achieved by agricultural extension workers which is an important aspect that plays a role in work success and goal achievement. Performance is measured based on the abilities possessed by an individual in the form of cognitive, affective and psychomotor aspects. The numbers of agricultural extension workers in the Sampara subdistrict under the supervision of the Agricultural Extension Center (BPP) of Sampara District are 17 agricultural extension workers. The condition of agricultural extension workers in the Agricultural Extension Center varies in ages, education level and working experiences. The purpose of this study was to analyze the level of performance of field agricultural extension workers (PPL) and to analyze the relationship between the characteristics of extension workers and the performance of field agricultural extension workers (PPL) in Sampara Sub district, Konawe Regency. The study employed scoring method using likert scale meanwhile measurement correlation between the characteristics of extension workers and the performance of Agricultural Extension workers through non-parametric analysis of Spearman's rank correlation test. The results of the study showed that the performance of field agricultural extension officers was in a fairly good category while the education level factors had a significant or strong relationship as shown by the Rs coefficient with value of 0.721.